Inside outside : past and future of the anti-globalization movement : proceeding of the International Colloquim on Anti-globalism, Ghent, 9 september 2005 / Francine Mestrum & Donald Weber (eds.) - Mestrum, FrancineWeber, Donald (International Colloquium on Anti-globalism (2005. Gante, Bélgica))
Bibliografía: p. 98-106